THE BENEFITS AND CHALLENGES OF STUDYING ABROAD (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
Studying abroad offers numerous academic, personal, and professional benefits, but it also presents challenges that students must navigate to ensure a successful experience. This article examines the advantages of studying abroad, including cultural exposure, language acquisition, and global networking, while also addressing common obstacles such as cultural adjustment, financial considerations, and academic differences. By exploring relevant studies and expert opinions, this article provides a balanced overview of what prospective international students can expect, along with practical strategies for overcoming challenges. The growing trend of global education underscores the need for thorough preparation and adaptability, and this paper highlights the key factors that contribute to a fruitful study abroad experience.